AKTIVITAS ANTI BAKTERI EKSTRAK ETIL ASETAT KULIT KAYU AKWAY (Drimys piperita Hook. f.) DALAM KALDU DAGING SAPI SELAMA PENYIMPANAN - Gino Nemesio Cepeda, Meike Meilan Lisangan,Isak Silamba, Eka Sartika (Jurnal Teknologi Industri Pertanian, 2016)
Akway (Drimys piperita Hook.f.) is the woody, evergreen and aromatic plant that has been used for medical purpose to heal malaria and enhance vitality by Sougb tribe in Sururey village, District of Manokwari. The Previous study indicated that ethylacetate extract of D. piperita had stronger antibacterial activities than ethanol and hexane extracts. The objectives of this research were to determine antibacterial activities of akway bark extracton some concentrations, minimum inhibitory concentration (MIC) and effect of MIC on bacterial growth in beef broth during storage. Antibacterial activity assay was done using agar diffusion and broth dilution method. The results indicated that antibacterial capacity of extract increased with the concentration. MICs of extract to tested bacteria varied from 0.25% to 0.55%.  Extract concentration of 0.5 MIC (0.25%) inhibited bacterial growth in beef broth up to 20 days during room temperature storage while in refrigerator no growth identified up to 48 days. On the other hand, untreated beef broth stored in room temperature showed bacterial growth of 4.56 log cfu/mL in 12 hours whereas in refrigerator bacterial growth identified was 2.17 cfu/mL for 24 days storage. Keywords : antibacterial,  Drimys piperita, extract,